2016
DOI: 10.1111/cbdd.12829
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of neurotrophic agents based on hydroxycinnamic acid scaffold

Abstract: The number of people affected by neurodegenerative disorders such as Alzheimer's disease and Parkinson's disease is rapidly increasing owing to the global increase in life expectancy. Small molecules with neurotrophic effects have great potential for management of these neurological disorders. In this study, different (C1-C12) alkyl ester derivatives of hydroxycinnamic acids (HCAs) were synthesized (a total of 30 compounds). The neurotrophic capacity of the test compounds was examined by measuring promotion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…These results suggest involvement of inhibition of apoptotic and necrotic processes in the neuroprotective action of MC. It should be noted that previous studies demonstrated that CA or its derivatives inhibited apoptotic processes in neuronal cells which were induced by various factors (e.g., low potassium level, H 2 O 2 , serum deprivation) [ 5 , 8 , 13 , 19 , 40 ] and our present results extend these data by showing the effects of MC in the oxidative stress-based model. It is also in line with previous data from non-neuronal cells (kidney epithelium cell line LLC-PK) where MC (100 μM) reduced the contrast-induced caspase-3 activity and increased cell survival [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These results suggest involvement of inhibition of apoptotic and necrotic processes in the neuroprotective action of MC. It should be noted that previous studies demonstrated that CA or its derivatives inhibited apoptotic processes in neuronal cells which were induced by various factors (e.g., low potassium level, H 2 O 2 , serum deprivation) [ 5 , 8 , 13 , 19 , 40 ] and our present results extend these data by showing the effects of MC in the oxidative stress-based model. It is also in line with previous data from non-neuronal cells (kidney epithelium cell line LLC-PK) where MC (100 μM) reduced the contrast-induced caspase-3 activity and increased cell survival [ 54 ].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in the present study we found that the calpain inhibitor, MDL28170 protected cells against oxidative stress-induced cell damage to a smaller extent than MC and the protection range was not changed after administration of both compounds which suggests possible involvement of calpain inhibition in the MC-mediated neuroprotection. There are conclusive data showing the participation of activation of the pro-survival PI3-K/Akt pathway in the neuroprotective effects of CA and/or its derivatives [ 5 , 6 , 7 , 22 ]. However, in our study the inhibitor of PI3-K, LY294002 failed to block the neuroprotective effects of MC in the H 2 O 2 model of cell damage which excludes the participation of this signaling pathway in the MC-mediated neuroprotection at least in this model of neuronal injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations